2016
DOI: 10.18585/inabj.v8i3.231
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial Activity of Eel (Anguilla spp.) Mucus against Salmonella typhi

Abstract: BACKGROUND: Typhoid fever has become one global health problem. Typhoid fever is caused by a Gram-negative bacterium, Salmonella typhi. Eel (Anguilla spp.) is a fish which lives in the sea or in freshwater. Several previous studies have found that Anguilla spp. mucus has the ability as antibacterial against Gram-positive and negative. Although the antibacterial activity of Anguilla spp. against various pathogens had been reported, very little is known about its activity against Salmonella typhi. The aim of thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 3 publications
(3 reference statements)
0
3
0
Order By: Relevance
“…Present results on antibacterial activity shown by selected exotic carps also confirm that fish mucus is a source of antimicrobial products. Earlier studies by many authors (Balasubramanian et al 2012;Prakash et al 2013;Nurtamin et al 2016) have also demonstrated strong antibacterial activity in several fishes. Ebran et al (2000) stated that only the hydrophobic components of crude epidermal mucus of fresh water and sea water fish exhibited strong pore-forming properties, which were well correlated with antibacterial activity.…”
Section: Discussionmentioning
confidence: 84%
“…Present results on antibacterial activity shown by selected exotic carps also confirm that fish mucus is a source of antimicrobial products. Earlier studies by many authors (Balasubramanian et al 2012;Prakash et al 2013;Nurtamin et al 2016) have also demonstrated strong antibacterial activity in several fishes. Ebran et al (2000) stated that only the hydrophobic components of crude epidermal mucus of fresh water and sea water fish exhibited strong pore-forming properties, which were well correlated with antibacterial activity.…”
Section: Discussionmentioning
confidence: 84%
“…), Asian swamp eel (Monopterus albus), and marine stingray were reported using antibacterial mechanisms through their skin which also have potential effects against pathogenic bacteria such as Salmonella spp. (Bragadeeswaran and Thangaraj 2011;Vennila et al 2011;Nurtamin at al. 2016;Hilles et al 2018).…”
Section: Resultsmentioning
confidence: 99%
“…Hence, this test reported that E. coli showed higher inhibition zones than S. aureus since the mucus extracts can penetrate more easily on E. coli cell walls than S. aureus [13]. Nurtamin et al (2016) reported that eel mucus also can be used to treat typhoid fever [14]. According to Tee (2002), typhoid fever is a contagious illness that can spread quickly through contaminated foods and polluted water caused by Salmonella typhi [22].…”
Section: Anguilla Japonicamentioning
confidence: 99%
“…In Fig. 5, Nurtamin et al (2016) reported that the aqueous extract collected from Anguilla spp. was tested against S. typhi.…”
Section: Anguilla Japonicamentioning
confidence: 99%

Antimicrobial Activity of Eel Mucus: A Review

Nur Afiqah Azaldin,
Liyana Azmi,
Muhamad Arif Mohamad Jamali
et al. 2023
MJoSHT